2008
DOI: 10.2135/cropsci2008.01.0031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flavonoids in Flower Petals of Soybean Flower Color Variants

Abstract: We previously identified two anthocyanins, malvidin 3,5‐di‐O‐glucoside and delphinidin 3,5‐di‐O‐glucoside, in flower petals of soybean cultivars with purple flowers, ‘Harosoy’ and ‘Clark’. However, two other anthocyanins found by high performance liquid chromatography (HPLC) analysis could not be identified. We further evaluated the effects of flower color genes W1, W3, W4, and Wm on flavonoid components using near‐isogenic lines for these genes. The first objective of this study was to determine the two unide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
(36 reference statements)
7
23
0
Order By: Relevance
“…Studies of the standard (banner) petals of purple-flowered soybean cultivars show that these have a different sugar moiety at the 3 position of the C ring of their anthocyanidins compared with pea: the primary anthocyanins detected in soybean cv Clark (W1W1 w3w3 W4W4 WmWm TT TdTd) and cv Harosoy (W1W1 w3w3 W4W4 WmWm tt TdTd) were malvidin, delphinidin, and petunidin 3,5-di-O-glucoside and delphinidin 3-O-glucoside (Iwashina et al, 2008), whereas delphinidin and petunidin-3-rhamnoside-5-glucoside were the major anthocyanins found in the wing petals of pea line JI 2822 in this study, consistent with previous studies on line L 60 of pea (Statham et al, 1972). As the intensity of coloration in pea petals indicates (Fig.…”
Section: Flower Pigmentation In Pea and Soybeanmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the standard (banner) petals of purple-flowered soybean cultivars show that these have a different sugar moiety at the 3 position of the C ring of their anthocyanidins compared with pea: the primary anthocyanins detected in soybean cv Clark (W1W1 w3w3 W4W4 WmWm TT TdTd) and cv Harosoy (W1W1 w3w3 W4W4 WmWm tt TdTd) were malvidin, delphinidin, and petunidin 3,5-di-O-glucoside and delphinidin 3-O-glucoside (Iwashina et al, 2008), whereas delphinidin and petunidin-3-rhamnoside-5-glucoside were the major anthocyanins found in the wing petals of pea line JI 2822 in this study, consistent with previous studies on line L 60 of pea (Statham et al, 1972). As the intensity of coloration in pea petals indicates (Fig.…”
Section: Flower Pigmentation In Pea and Soybeanmentioning
confidence: 99%
“…The wp allele is reported to contain a 5,722-bp CACTA transposable element in intron 2 of a F3H gene, F3H1, with down-regulated expression (Zabala and Vodkin, 2005). A null mutation would result in a lack of the substrates dihydromyricetin, dihydrokaempferol, and dihydroquercetin required for conversion into anthocyanins (Grotewold, 2006;Iwashina et al, 2008); therefore, a null mutant would be expected to have white flowers and, indeed, white-flowered mutants have been observed in other plant species (Martin et al, 1991;Britsch et al, 1992). Analysis of a wp genotype obtained by back-crossing to soybean cv Loda showed that the wp line had a low flavonoid content: 9% of the total flavonol glycosides, no detectable kaempferol 3-O-glucoside, and 28% of dihydroflavonols compared with cv Clark (Iwashina et al, 2008).…”
Section: Flower Pigmentation In Pea and Soybeanmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant cultivation, sampling, flavonoid extraction, and HPLC analysis were performed as previously described (Iwashina et al, 2007;Iwashina et al, 2008;Takahashi et al, 2010). Plant cultivation, sampling, flavonoid extraction, and HPLC analysis were performed as previously described (Iwashina et al, 2007;Iwashina et al, 2008;Takahashi et al, 2010).…”
Section: Analysis Of Flavonoidsmentioning
confidence: 99%
“…The flavonoids in purple petals of soybean and G. soja are similar (Iwashina et al, 2007;Iwashina et al, 2008;Takahashi et al, 2010). The primary anthocyanins are malvidin 3,5-di-O-glucoside, petunidin 3,5-di-O-glucoside, delphinidin 3,5-di-O-glucoside and delphinidin 3-O-glucoside.…”
mentioning
confidence: 93%